Down-Regulation of NDUFB9 Promotes Breast Cancer Cell Proliferation, Metastasis by Mediating Mitochondrial Metabolism - Li, Liang-Dong; Sun, He-Fen; Liu, Xue-Xiao; Gao, Shui-Ping; Jiang, Hong-Lin; Hu, Xin; Jin, Wei (PloS one, 2015)
Despite advances in basic and clinical research, metastasis remains the leading cause of death in breast cancer patients. Genetic abnormalities in mitochondria, including mutations affecting complex I and oxidative phosphorylation, are found in breast cancers and might facilitate metastasis. Genes encoding complex I components have significant breast cancer prognostic value. In this study, we used quantitative proteomic analyses to compare a highly metastatic cancer cell line and a parental breast cancer cell line; and observed that NDUFB9, an accessory subunit of the mitochondrial membrane respiratory chain NADH dehydrogenase (complex I), was down-regulated in highly metastatic breast cancer cells. Furthermore, we demonstrated that loss of NDUFB9 promotes MDA-MB-231 cells proliferation, migration, and invasion because of elevated levels of mtROS, disturbance of the NAD+/NADH balance, and depletion of mtDNA. We also showed that, the Akt/mTOR/p70S6K signaling pathway and EMT might be involved in this mechanism. Thus, our findings contribute novel data to support the hypothesis that misregulation of mitochondrial complex I NADH dehydrogenase activity can profoundly enhance the aggressiveness of human breast cancer cells, suggesting that complex I deficiency is a potential and important biomarker for further basic research or clinical application.